The Economic Impact of Expo 2020 Dubai on the UAE: Was It a Sustainable Boon? - Varghese, Deepa A (Digital Repository of Theses, 2024)
Background A mega event attracts significant number of participants, spectators, and media attention from around the world. Countries host mega events to boost economic growth, enhance global image, attract tourism, and foster national pride. These events generate significant infrastructure investments, create job opportunities, and stimulate local economies. Host countries set certain targets to measure the success of the event. This thesis analyses, the long-term economic impact of the Expo 2020 Dubai, on the host country, the United Arab Emirates. Many studies have performed evaluations on the impact, while the event is actually being held or even after the event; however, not much research has been done on the long-term impact on the country especially after the event has been delivered. Methods This study used a mixed methods approach, relying heavily on quantitative data to provide realistic evidence and also incorporated qualitative methods to capture contextual understandings that are equally important for a comprehensive evaluation. The structured interviews for qualitative methodology were conducted with five key stakeholders of Expo 2020 Dubai, to understand their expectations from the event. Results The data were analysed using financial planning tools to adjust the forecast based on actual post event achievements. The analyses are important as substantial investments and resources are allocated for such mega events and hence it is critical to study the long-term impact, as these impacts help to understand and allows for a more comprehensive evaluation of the event's effects. Discussion and Conclusion The thesis provides an in-depth analysis of the economic impact of Expo 2020 Dubai by examining key performance indicators and adjusting future forecasts based on post-event achievements. It explores the direct and indirect effects on the economy, highlighting contributions to economic growth, diversification, and long-term sustainability. These insights will enable country leaders to make more informed decisions when considering the hosting of future mega events. The study concludes that incorporating an impact assessment into the planning process of every mega-event is essential. Additionally, establishing strategies for impact equity and implementing mitigation plans to manage potential adverse effects are crucial components for ensuring the overall success and sustainability of such events. Expo 2020 Dubai has proven to be a sustainable boon, with ongoing benefits for the country. The event has positively impacted the nation's growth and development, continuing to yield economic and social advantages long after it ended. It also has set high expectations for future world expos.